EFEKTIVITAS TERAPI DZIKIR DALAM MENURUNKAN TINGKAT KECEMASAN PADA PENDERITA HIPERTENSI: KAJIAN LITERATUR - Mawaddah, Alfi Wirda; Lestari, Yuliana Intan; -, Harmaini (unprimdn.ac.id, 2024)
Dhikr therapy is effective in reducing anxiety levels and blood pressure in hypertensive patients. This study aims to explore the effectiveness of dhikr therapy in reducing anxiety in people with hypertension. The literature review was conducted by analyzing research articles that met the inclusion criteria, namely articles that discuss the effect of dhikr therapy as a relaxation method in individuals with hypertension, published in indexed journals and published in the last 10 years. The thematic analysis method was used to identify the main patterns of relevant research results. The results showed that dhikr therapy has a significant positive impact on reducing anxiety levels and improving emotional well-being in people with hypertension. Some studies have also shown a decrease in anxiety and stress, as well as improvements in blood pressure after regular dhikr practice. These findings suggest that dhikr can be an additional approach to the management of hypertension and anxiety, especially for populations seeking non-pharmacological interventions. However, further research is needed to corroborate its long-term effectiveness and optimal therapeutic techniques.